Anti-IL-5 treatment, but not neutrophil interference, attenuates inflammation in a mixed granulocytic asthma mouse model, elicited by air pollution - Joyceline De Volder; Annelies Bontinck; Valerie Haelterman; Louis Boon; Guy F. Joos; Guy G. Brusselle; Tania Maes (Respiratory Research)
Abstract Introduction Diesel exhaust particles (DEP) have been proven to aggravate asthma pathogenesis. We previously demonstrated that concurrent exposure to house dust mite (HDM) and DEP in mice increases both eosinophils and neutrophils in bronchoalveolar lavage fluid (BALF) and also results in higher levels of neutrophil-recruiting chemokines and neutrophil extracellular trap (NET) formation compared to sole HDM, sole DEP or saline exposure. We aimed to evaluate whether treatment with anti-IL-5 can alleviate the asthmatic features in this mixed granulocytic asthma model. Moreover, we aimed to unravel whether neutrophils modulate the DEP-aggravated eosinophilic airway inflammation. Material and methods Female C57BL6/J mice were intranasally exposed to saline or HDM and DEP for 3 weeks (subacute model). Interference with eosinophils was performed by intraperitoneal administration of anti-IL-5 (TRFK5), which neutralizes IL-5. Interference with neutrophils and neutrophil elastase was performed by intraperitoneal anti-Ly6G and sivelestat administration, respectively. Outcome parameters included eosinophils subsets (homeostatic EOS and inflammatory EOS), proinflammatory cytokines, goblet cell hyperplasia and airway hyperresponsiveness. Results The administration of anti-IL-5 significantly decreased eosinophilic responses, affecting both inflammatory and homeostatic eosinophil subsets, upon subacute HDM + DEP exposure while BAL neutrophils, NET formation and other asthma features remained present. Neutrophils were significantly reduced after anti-Ly6G administration in BALF, lung and blood without affecting the eosinophilic inflammation upon HDM + DEP exposure. Sivelestat treatment tended to decrease BALF inflammation, including eosinophils, upon HDM + DEP exposure, but did not affect lung inflammation. Conclusion Inhibition of IL-5 signalling, but not neutrophil interventions, significantly attenuates eosinophilic inflammation in a mouse model of mixed granulocytic asthma, elicited by air pollution exposure.